Anion Recognition and Induced Self‐Assembly of an α, γ‐Cyclic Peptide To Form Spherical Clusters. (4th March 2016) - Rodríguez‐Vázquez, Nuria; Amorín, Manuel; Alfonso, Ignacio; Granja, Juan R.
Abstract: A cyclic octapeptide composed of hydroxy‐functionalized γ‐amino acids folds in a "V‐shaped" conformation that allows the selective recognition of anions such as chloride, nitrate, and carbonate. The process involves the simultaneous self‐assembly of six peptide subunits and the recognition of four anions to form a tetrahedral structure, in which the anions are located at the corners of the resulting structure. Each anion is coordinated to three different peptides. The structure was fully characterized by several techniques, including NMR spectroscopy and X‐ray diffraction, and the material was able to facilitate the transmembrane transport of chloride ions.